Outcomes following resection of intrahepatic cholangiocarcinoma. Issue 4 (14th November 2014) - Tabrizian, Parissa; Jibara, Ghalib; Hechtman, Jaclyn F.; Franssen, Bernardo; Labow, Daniel M.; Schwartz, Myron E.; Thung, Swan N.; Sarpel, Umut
Abstract Objectives The aim of this analysis was to examine prognostic features and outcomes in patients undergoing resection for intrahepatic cholangiocarcinoma (ICC). Methods A retrospective chart review was performed in all patients who underwent R0 or R1 resection for primary ICC between 1995 and 2011. Clinical data were abstracted and statistical analyses were conducted in the standard fashion. Results A total of 82 patients underwent curative hepatectomy for primary ICC; 51 patients in this cohort developed recurrence. The median follow‐up of survivors was 27 months (range: 1–116 months). Recurrences were intrahepatic (65%), associated with multiple tumours (54%) and occurred during the first 2 years after hepatectomy (86%). The main factor associated with recurrence after resection was the presence of satellite lesions. Overall 5‐year disease‐free survival after primary resection was 16%. Factors associated with poor survival were transfusion and perineural invasion. Treatment of recurrence was undertaken in 89% of patients and repeat surgical resection was performed in 15 patients. The 3‐year survival rate after recurrence was 25%. Prolonged survival after recurrence was associated with a solitary tumour recurrence. Conclusions Despite curative resection of ICC, recurrence can be expected to occur in 79% of patients at 5 years. Predictors of survival and recurrence after resection vary in the literature. In patients with recurrence, selection of the optimal treatment remains challenging.